THE MARKETING MIX EFFECT OF INTERESTS IN HIGH SCHOOL STUDENTS CHOOSE NATIONS CHILDREN CHRISTIANITY SURABAYA - Sukoco, Agus (Economic and Bussiness Faculty, Dr Soetomo University, 2016)
Abstract.This study aims to determine how much influence the marketing mix to the acquisition decision a student at the College of Christian Religion AnakBangsa. The research model used in this research that using a questionnaire (questionnaire), the sample in this study 81 students who were students Nations Children STAK. The analytical method used is multiple regression analysis. From the results of the study indicated that there is the influence of simultaneous perception of the marketing mix to the acquisition STAK Nations Children student in Surabaya. Where the value of the highest simultaneously shown on variable X5 is people, with a value of 0.658 or 65.8%, to the presentation of student acquisition. Partially perception there are four variables, namely the product variable (X1)with a value of 0.647 or 0.647%, the variable price (X2)with a value of 0.601 or 60.1%, variable promotions (X3)with a value of 0.611 or 61.1% and variable locations ( X4)with a value of 0.658 (65.8%) were the most influential in the interest of students. Besides the variable (X5)is a dominant influence on the variable interest of students choose STAK AnakBangsa Surabaya.Keywords: Marketing Mix, Interests Student